The Impact of Inventory Managementon Customer Satisfaction at Apotik Global Medan - Deva Djohan; Stefvy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
One of the most important aspects of any business is inventory management. While inventory management has always been important, it has become more important over the past several decades. Inventory management has issues that affect customer satisfaction levels. Many large retailers are expecting manufacturers to provide them with perfect order deliveries. The writer will conduct research in Apotik Global Medan. Apotik Global Medan is a family business whose core business is a drug store which provide many kind sof medicines for individulas, hospitals, and doctors’ prescriptions. When the customers order and look for the medicines, the products are not available and the customers will feel dissapointed with the unavailability of the medicines they need. The problem identifications are Is there any impact between inventory management and customer satisfaction at Apotik Global Medan? How strong does the impact of inventory management on customer satisfaction at Apotik Global Medan? In research design, the population that the writer will use the most error inputs which are occured in July, August, and September 2013, the total customers in July, August and September 2013 of Apotik Global Medan are 800 people. The writer will use 10% of 800 people is 80 customers. In analyzing data, the writer used some methods such as statistics, validity test, reliability test, normality test, correlation test, determination test, linier regression, and hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result of 0.78 which inventory management has a strong towards customer satisfaction at Apotik Global Medan. From the calculation of hypothesis test, zcount= 7.09.The zcount > ztable (7.09>1.96), This means the Null hypothesis (Ho) is rejected. Inventory Management do have impact on customer satisfaction at Apotik Global Medan.